STRATEGI GURU BK DALAM PEMBERIAN LAYANAN KONSELING TERHADAP KEBIASAAN ANAK BERBICARA KASAR DI SDN LAE SIMOLAP - Putri Hanah Anggara; Roma Ulinnuha (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to determine the counseling teacher's strategy in providing counseling services to children's speaking habits at SDN Lae Simolap. This research is a qualitative descriptive research. The data sources in this study were 2 counseling teachers who provided counseling services and several students at SDN Lae Simolap. Data collection techniques with direct observation and interviews. The results of this study indicate that the counseling teacher's strategy in providing counseling services to children's speaking habits is by individual counseling services through practicing the habit of speaking politely to teachers, friends and the surrounding environment for a certain period of time, consulting with certain parties to help and monitor and direct students to develop good behavior, and conduct home visits when absolutely necessary. The results obtained in the implementation of this counseling have been going well and have been able to reduce the behavior of speaking rudely to students at SDN Lae Simolap.